Current views and challenges on clinical cholera - Somboonwit, Charurut (Bioinformation, 2017)
Cholera, an acute diarrheal infection has become a major global threat. Vibrio cholerae the causative agent of cholera has been responsible for six previous pandemics since 1817 that spanned four continents and Australia with the seventh pandemic ongoing since 1961. Two serogroups of V. cholerae O1 and O139 have the ability to secrete the enterotoxin with potential to cause epidemics. The prior six pandemics were caused by the classical biotype of the O1 serogroup. However, the emergence of the El Tor biotype and subsequent variants of El Tor with classical traits are the main isolates in the seventh pandemic. Cholera outbreaks have increased among vulnerable communities affected by war, earthquakes, conflicts and famines. Annually, 2.9 million cases of cholera occur globally in 69 endemic countries with 95,000 deaths. Early detection followed by prompt fluid and electrolyte replacement can reduce the case fatality ratio significantly. Improvements in water systems, sanitation and hygiene have effectively eliminated the transmission of cholera in high-income countries and reduced transmission in some developing nations. However, an estimated 1.8 billion are still at risk for cholera due to lack of potable water, inadequate sanitation and hygiene. Interventions focusing on hygiene in conjunction with proper disposal and treatment of sewage and provision of safe drinking water are likely to be effective in preventing the recurrence of cholera. Lastly, the use of current oral vaccines in endemic settings in combination with WASH interventions may be an effective approach to prevent and reduce the spread of cholera infection.